Analisis Kritik Terhadap Pelaksanaan Pembelajaran PAI di Sekolah - Shalahudin Ismail Ismail; Asep Saepulmillah; Uus Ruswandi; Bambang Samsul Arifin (Jurnal Pendidikan Islam, 2020)
The purpose of this study was to analyze the implementation of Islamic Education learning in schools. The method used in this research is library research, where the author bases on data sources or references in the form of text from the opinions of experts that have been formulated in the form of books, journals, and others. The results show that the critical analysis in the implementation of Islamic Education learning in schools is that the level of concern of the teachers to present a good and systematic planning, implementation and evaluation of learning, and their level of expertise in their respective scientific disciplines is not sufficient to be able to design a learning concept. The solution in the implementation of effective Islamic education learning is that Islamic education teachers must have the ability to understand the characteristics and desires of their students through the use of various methods that can arouse student creativity so that they can be motivated to learn Islamic education. Also the teacher must be communicative so that it can adapt to the conditions of the students. The teacher must also provide opportunities for students to express opinions so that a learning process occurs which is not only a transfer of material from teacher to student but also a reciprocal process between the two.